2007
DOI: 10.1097/coh.0b013e3280f3bfe2
|View full text |Cite
|
Sign up to set email alerts
|

Capturing viral diversity for in-vitro test reagents and HIV vaccine immunogen design

Abstract: These recent findings and newly developed strategies that allow more comprehensive detection of HIV-specific T-cell responses provide the tools necessary to assess vaccine immunogenicity and breadth within genetically different host populations and relative to diverse local viral populations. They will ultimately inform design of vaccine immunogen sequences that can induce broadly protective cellular immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…These studies highlight the importance of engineering Env immunogens that elicit a broader and more effective recognition of variant Env species compared with that achieved with an Env immunogen from a single viral isolate. Currently, the use of engineered ancestral or consensus Env sequences are being evaluated as immunogens to elicit immune responses (humoral and cellular) that can recognize a broad spectrum of HIV-1 variants within and between clades (18,49). An important aspect of the current experimental design is that the variant challenge virus envelopes reflected a valid ancestor relationship that is representative of the natural evolution observed in HIV-1 infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies highlight the importance of engineering Env immunogens that elicit a broader and more effective recognition of variant Env species compared with that achieved with an Env immunogen from a single viral isolate. Currently, the use of engineered ancestral or consensus Env sequences are being evaluated as immunogens to elicit immune responses (humoral and cellular) that can recognize a broad spectrum of HIV-1 variants within and between clades (18,49). An important aspect of the current experimental design is that the variant challenge virus envelopes reflected a valid ancestor relationship that is representative of the natural evolution observed in HIV-1 infections.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the effect of Env variation on antigenic properties indicate that even minor changes in amino acid sequence can dramatically alter antibody and CTL specificities in in vitro assays and immune control of persistent infections in vivo (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Nevertheless, even apparently extensive Env variations may not necessarily cause detectable changes in immune phenotype as measured by in vitro assays alone (18).…”
mentioning
confidence: 99%
“…For this reason, different test antigen design strategies, trying to cope with the diversity of circulating viral isolates in a single sequence, have been developed in the past. These strategies include central sequence designs such as Center of Tree (COT) [ 28 , 29 , 30 , 31 , 32 ], Ancestral [ 33 , 34 , 35 , 36 ] or Consensus sequences [ 29 , 30 , 31 , 32 , 35 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]; which may (Ancestral, COT) or may not (Consensus) represent naturally occurring sequences of replication competent viruses. All these designs are sensitive to the underlying sequence database and may change over time as new sequence information on additional isolates becomes available.…”
Section: Introductionmentioning
confidence: 99%
“…All these designs are sensitive to the underlying sequence database and may change over time as new sequence information on additional isolates becomes available. Direct comparisons of these different central sequence approaches have been performed for a highly variable pathogen (human immunodeficiency virus, HIV) and shown that the different designs yielded comparable results when synthetic peptides covering these sequences were used to measure virus-specific T cell responses [ 42 , 43 ]. However, the additional costs in terms of peptide synthesis and cells needed for ex-vivo experiments, may not warrant inclusion of all the different variants into a single test set.…”
Section: Introductionmentioning
confidence: 99%